Breaking the cycle with trauma-focused mentalization-based treatment: theory and practice of a trauma-focused group intervention - Smits, Maaike L.; de Vos, Jasmijn; Rüfenacht, Eva; Nijssens, Liesbet; Shaverin, Lisa; Nolte, Tobias; Luyten, Patrick; Fonagy, Peter; Bateman, Anthony (Frontiers in Psychology, 2024)
is an adaptation of MBT specifically developed for patients suffering from attachment or complex trauma, with the possibility of cooccurring borderline personality pathology. The creation of MBT-TF was driven by previous research and observations that interventions centered on mentalizing could be significantly improved by directly addressing the impact of trauma. MBT-TF aims to mitigate symptoms that arise post-trauma, such as hyperarousal, hypervigilance, intrusions, flashbacks, avoidance behaviours, dissociative experiences, negative perceptions of self and others, and ensuing relational difficulties. Implemented as a group intervention, MBT-TF typically spans 6-12 months. From a mentalization perspective, trauma, particularly attachment trauma, leads to a failure in processing the effects of trauma through and with others. Stress and attachment behavioural systems are disrupted, which undermines the capacity for epistemic trust, and impairs mentalizing abilities. This paper offers a concise summary of the reasoning for MBT-TF's creation, its theoretical underpinnings, and its clinical strategy for addressing the adverse impacts of trauma. It further details the treatment phases, their main goals, and interventions, supplemented by clinical case examples that underscore MBT-TF's distinctive attributes and frequent clinical hurdles. Introduction: the rationale for MBT-TF A significant proportion of mental health patients report having experienced adversity during childhood and later life (Lippard and Nemeroff, 2020, Horowitz et al., 2000, McKay et al., 2021). Studies have consistently highlighted a strong link between such adversity and various forms of psychopathology, noting that trauma significantly influences current functioning and treatment outcomes (